A música para violão solo de Edino Krieger: um estudo do idiomatismo técnico-instrumental e processos composicionais - Kreutz, Thiago de Campos (2014)
This thesis is about the five solo-guitar works composed by brazilian composer Edino Krieger: Prelúdio, Ritmata, Romanceiro, Passacalha para Fred Schneiter and Alternâncias. As these works present notorious functionality and effect on the instrument, we seek to understand how the composer uses the idiossyncratic caracteristics of the guitar in writing for this instrument. Thus, we discuss the relationship involving the composer, the refered works and the instrument. The work itself is divided in three parts. In the first we present biographical data, compositional caracteristics, works and the relationship between the composer and the classical guitar. In the second the compositional process used in the works is discussed, as well as their recurrence in the presented compositions. For this analysis the used methods were the analytical precepts proposed by John White (1976). In the third part we discuss the use and application of “idiomatism” as and applicable term in the field of music studies. To evidentiate the use of idiomatic elements of the guitar in the works of Edino Krieger, the method used was that proposed by Fábio Scarduelli (2007) – two distinct aspects of idiomatism: “implicit” and “explicit”.